2013
DOI: 10.1093/annhyg/met053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Breathing Frequency and Flow Rate on the Total Inward Leakage of an Elastomeric Half-Mask Donned on an Advanced Manikin Headform

Abstract: Objectives The objective of this study was to investigate the effects of breathing frequency and flow rate on the total inward leakage (TIL) of an elastomeric half-mask donned on an advanced manikin headform and challenged with combustion aerosols. Methods An elastomeric half-mask respirator equipped with P100 filters was donned on an advanced manikin headform covered with life-like soft skin and challenged with aerosols originated by burning three materials: wood, paper, and plastic (polyethylene). TIL was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…This finding is consistent with our previous studies, which were conducted using elastomeric half-mask with P100 filters. (6,18)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with our previous studies, which were conducted using elastomeric half-mask with P100 filters. (6,18)…”
Section: Resultsmentioning
confidence: 99%
“…Three types of combustion particles, including wood, paper and plastic, were generated in a test chamber by burning a wood stick (24 cm long and 0.4 cm diameter, 1.9 ± 0.5 g), a sheet of paper (23 × 24 cm brown multifold paper towel, 2.1 ± 0.2 g), and a plastic straw (19 cm long and 0.5 cm diameter, 0.6 ± 0.01 g), respectively, using the protocol described elsewhere. (6) The burning materials were held by a caliper with a water-filled basin right under it, and were ignited by a lighter. The measurement was started 15 min (= time zero) after the complete burning of each material to allow the particles to reach a uniform concentration inside the test chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plastic straw was ignited by a lighter and left for burning until completely consumed. The sampling devices were started to collect data 15 min after the completion of the plastic burning, which allowed the plastic particles to reach a spatial uniformity (He et al , 2014a). We were specifically interested in testing the plastic particles as our previous study showed that they penetrated through the N95 FFR filters more readily than the other two types of combustion particles (wood and paper) (Gao et al , 2015).…”
Section: Methodsmentioning
confidence: 99%
“…[9] In addition, annual fit-testing is required for N95 FFRs since face seal leakage would significantly affect the achieved protection. [10,11]…”
Section: Introductionmentioning
confidence: 99%